Extraction of Eugenol from Clove Buds and Testing its Antimicrobial Activity - Shrestha, Nawaraj; Upadhyaya, Tika Prasad (Academic Journal of Sukuna, 2025)
Eugenol, the primary component of clove oil, is a natural compound produced by Eugenia caryophyllata for protection against microorganisms and pests. Due to its easy isolation and potential as an antimicrobial medicine, eugenol has gained interest in the medical and food industries. This interest is driven by the negative perception of synthetic drugs and the traditional use of plant-based medicines. As a result, a project was conducted to assess the antimicrobial activity of eugenol against various human pathogenic bacteria and fungus. The test organisms included both Gram-positive bacteria e.g., Bacillus spp., Streptococcus pyogenes, and methicilline-resistant Staphylococcus aureus (MRSA) and Gram-negative bacteria (e.g., Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Shigella sonnei). Additionally, Aspergillus genus fungus was used. Eugenol was isolated from hydro-distilled clove oil, and three different concentrations of the test solution were prepared: 1% (v/v), 0.5% (v/v), and 0.25% (v/v). The antimicrobial activity of eugenol was evaluated by applying 100μl of each eugenol concentration to wells made in Muller Hinton agar (MHA) and Potato dextrose agar (PDA) plates, on which the pathogens were swabbed. The results displayed a positive outcome, as evidenced by the presence of a zone of inhibition indicating the inhibition of microbial growth. Overall, the study demonstrated the antimicrobial effectiveness of eugenol against various microorganisms, including Gram-positive and Gram-negative bacteria, as well as the Aspergillus genus of fungus. These findings highlight the potential of eugenol and similar phytochemicals in the development of antimicrobial medicines and their applications in the food industry for safety and preservation purposes.